High-temperature deformation behavior and concurrent microstructural evolution in novel Ni-based compositionally complex alloy - Ananya Chattree; Amrit Pandey; Saurabh S. Nene; Jaiveer Singh (Journal of Alloys and Metallurgical Systems)
In this study, a novel Ni46.8Fe23Co10V7(Al, Si)6.6 compositionally complex alloy (Ni-CCA) has been designed by merging the CALPHAD approach with the theoretical concepts (enthalpy of mixing, atomic radius mismatch parameter, valence electron concentration (VEC), and pair sigma forming elements (PSFE)). The theoretical analysis and the CALPHAD modeling predict the formation of a single FCC phase at room temperature along with the absence of TCP phases in the designed Ni-CCA. Subsequently, the pseudo-binary phase diagram obtained from Thermo-Calc through the latest HEA database predicts the presence of newer strengthening ordered phases containing Ni-Al-Si at elevated temperatures in Ni-CCA. Microstructural characterization of as-cast Ni-CCA displayed the formation of γ-FCC phase dominated microstructure containing a minor fraction of BCC phase at room temperature whereas high-temperature compression depicted synergistic precipitation of Ni-Al-Si containing L12 type precipitate and dynamic recovery/recrystallization events during deformation leading to a marginal drop in yield strength (YS) at 800 °C. Moreover, the formation of necklace microstructure in a deformed specimen confirms the occurrence of dynamic recrystallization (DRX) in novel Ni-CCA.